Nymphs of the Oriental cockroach (Blatta orientalis) as passive vectors of causal agents of avian tuberculosis and paratuberculosis - Fischer, O A; Matlova, L; Dvorska, L; Svastova, P; Pavlik, I (Medical and veterinary entomology, 2003)
The potential transmission of the causal agent of paratuberculosis Mycobacterium avium ssp. paratuberculosis and avian tuberculosis Mycobacterium avium ssp. avium (Actinomycetales: Mycobacteriaceae) by nymphs of the Oriental cockroach Blatta orientalis L. (Blattodea: Blattidae) was investigated by oral infection with mycobacterial suspensions and examination of their droppings and bodies. Both the subspecies of M. avium were isolated from droppings at 3 days post-infection and M. a. avium was found in homogenized bodies at 10 days post-infection. The identity of M. a. avium and M. a. paratuberculosis isolates was demonstrated by Restriction Fragment Length Polymorphism (RFLP) analysis. The M. a. avium isolate used as the inoculum and the isolates from the bodies and droppings of the nymphs were shown to be virulent in chickens. The results show that orally infected nymphs of B. orientalis can harbour and shed viable and virulent mycobacteria. This hazard should be considered in the implementation of control measures against mycobacterial infections of animals and humans, which should include destruction of all developmental stages of cockroaches and prevention of their access to materials that can be contaminated by mycobacteria.
Keywords: Feces; Mycobacterium avium subsp. paratuberculosis; polymorfismus délky restrikčních fragmentů; Tuberculosis, Avian; Cockroaches; Birds; paratuberkulóza; Paratuberculosis; Insect Vectors; zvířata; feces; Humans; Polymorphism, Restriction Fragment Length; Mycobacterium avium; ptáci; švábi; hmyz - vektory; ptačí tuberkulóza; lidé; Animals